Vpliv toplotne obdelave na sorpcijske lastnosti lesa - Gorišek, Željko (Les (Ljubljana), 2004)
Shrinkage and swelling of wood in changing climate conditions depends on their sorption characteristics. This can be changed during different processes and treatments. The influence of temperature on tree levels (T1 = 20 °C, T2 = 100 °C in T3 = 180 °C) and two different times (t1 = 5 min. in t2 = 10 min.) of treatment on equilibrium moisture content (EMC) of wood during desorption and adsorption process at five level of relative humidity (j1 = 20 %, j2 = 33 %, j3 = 44 %, j4 = 65 % in j5 = 88 %) were examined. Sorption capacity decreased as temperature increased in all humidity range and at the higher level of humidity also other parameters and their interaction were statistically significant. Dent model of sorption isotherms was fitted to experimental data
Keywords: vlažnost lesa; sorpcijske lastnosti; modeli